EVALUATION OF PERFORMANCE LECTURER ON IMPLEMENTING TRIDHARMA COLLEGE - Joni Bungai; Indra Perdana (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
Lecturer performance expected to produce a professional lecturer and has good performance in implementing Tridharma college. The purpose of this study was to evaluate performance of Lecturer in (1) Education and Teaching, (2) Reseach, and (3) Performance of Community Service. This study was the evaluation of the program. This evaluation of Research lecturers performance, performance evaluation use model of 360 degrees (360 Degree Performance Appraisal Model). In general evaluation model aims to measure whether the performance lecturers carry out Tridharma accordance with the standard or predefined performance criteria. Research Subject of this Reseach are Lecturer in Faculty Of Teacher Training And Education State University of Palangka Raya.The Results (1) Performance Implement The Education And Teaching Are Good, Lecturer Applying Various Methods Of Learning (2) Performance Of Conducting Research Is Fairly Well, (3) Performance Of Community Service Is Good, Not Many Published. It Hoped In The Future The Lecturer In Faculty Of Teacher Training And Education State University of Palangka Raya Can Do More Better. Keywords: Lecturers, Performance of Lecturer, Tridharma College, Faculty of Teacher Training And Education State University of Palangka Raya